Pengaruh Kepemimpinan, Stres Kerja Dan Motivasi Terhadap Kinerja Pegawai Dinas Perhubungan Kabupaten Ogan Komering Ulu - Rani Anwar (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
This study aims to determine the influence of leadership, job stress and motivation on employee performance at Departmen of Transportation Ogan Komering Ulu Regency. In conducting the analysis used Multiple Linear Regression Analysis Method. Based on data analysis and discussion partially leadership (X1) has an influence on employee performance (Y), with the results Tcount (7.549) > Ttable (2.06866), job stress(X2) has an influence on employee performance (Y), with the results of Tcount (5,115) > Ttable (2,06866), and motivation(X3) has an influence on employee performance (Y), with the results of Tcount (2,816) >Ttable (2,06866). Meanwhile, Simultaneously leadership, job stress and motivation on employee performance at Departmen of Transportation Ogan Komering Ulu Regency with the results Fcount (305.311) >Ftable (3.03). The value of the coefficient of determination (R Square) is (0.972). This shows that the influence of leadership, job stress and motivation on employee performance at Departmen of Transportation Ogan Komering Ulu Regency, is 97.2% while the remaining 2.8% is influenced by other variables not explained in this study such as work involvement and work performance (Afandi, 2021:77).